RANCANG BANGUN APLIKASI HELPDESK DENGAN PENDEKATAN KNOWLEDGE MANAGEMENT SYSTEM SMAN 99 JAKARTA - Susanto, Lulu Kamila; Nurmiati, Evy (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
State High School 99 Jakarta is an educational institution that has a role in providing quality teaching, knowledge, and education for students. In the current digital era, knowledge is something that must be managed by an agency, especially an educational institution. In implementing this, an implementation of information technology is needed, namely the online-based Knowledge Management System software. In the education sector, a Hepldesk application helps a lot in improving performance and expertise. The purpose of this helpdesk application is to help facilitate the work problems of the school technician. In addition, the helpdesk application makes it easier for students to report damaged school facilities, so that the technician will immediately make repairs as soon as possible. The method used in building the helpdesk application is by using the Waterfall Model and designed using Unified Modeling Language (UML) diagrams. With the construction of this helpdesk application using a knowledge management system approach, it is hoped that it can be a tool to help manage damage reports as well as the perfect solution to solve the problem. damage according to the existing knowledge base.